La recherche archéologique et le patrimoine au Sultanat d’Oman comme facteurs de modernisation du pays - Sterenn Le Maguer (Arabian Humanities)
This article aims to show the role of archaeological research and heritage enhancement in the political, social and economic development of the Sultanate of Oman. Although archaeological research in the Sultanate of Oman began well before the accession to the throne of Sultan Qaboos bin Said Al Said, it became a real political and social issue during his reign. Archaeological excavations were first entrusted to Western researchers (mostly from institutions located in the United States, Great Britain, France, Italy or Germany), thus contributing to the country's emergence on the international scene. The Sultanate now has its own archaeological service and trains Omani archaeologists. This archaeological research will not only shed light on the Prehistory and history of this territory, it will also define a heritage that will mark the identity of the Sultanate of Oman. The Omani heritage is highlighted by the inscription of five sites on the Unesco World Heritage List between 1987 and 2018. This heritage, unique in the Gulf region, is a response to the choice of high-end tourism development in order to diversify the country's economy. The Sultanate of Oman is thus building the image of an open and culturally rich country to which UNESCO, an internationally recognised institution, provides a choice guarantee. At the same time, university courses in the fields of culture and heritage are offered to encourage young Omanis to work in the tourism sector. The development of this sector has also contributed to the modernisation of the country and its infrastructure in order to link the most important sites to the capital, Muscat, thus opening up previously isolated regions.